2021
DOI: 10.1155/2021/2895659
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng Saponin Promotes Bone Regeneration in Distraction Osteogenesis via the TGF-β1 Signaling Pathway

Abstract: Distraction osteogenesis (DO) is an efficient strategy that is employed for the treatment of large bone defects in craniomaxillofacial surgery. Despite its utility, however, DO is associated with a prolonged consolidation phase and a high complication rate that hinder its more widespread utilization. Panax notoginseng saponin (PNS) is a traditional Chinese medicine that is frequently administered for the treatment of a range of conditions. Herein, we explored the ability of PNS treatment to influence osteogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These analyses revealed that PNS was capable of enhancing mandibular generation and BMSC osteogenesis, upregulating osteogenesis-related genes at the mRNA levels through the modulation of the Smad/TGF-beta1 pathway. To sum up, these results proved the PNS as a potential and cost-effective therapeutic tool ( Liu et al, 2021 ). However, a single experiment lacks credibility, and further in-depth experiments are essential to confirm the relationship between PNS with DO.…”
Section: Pharmacological Therapymentioning
confidence: 77%
“…These analyses revealed that PNS was capable of enhancing mandibular generation and BMSC osteogenesis, upregulating osteogenesis-related genes at the mRNA levels through the modulation of the Smad/TGF-beta1 pathway. To sum up, these results proved the PNS as a potential and cost-effective therapeutic tool ( Liu et al, 2021 ). However, a single experiment lacks credibility, and further in-depth experiments are essential to confirm the relationship between PNS with DO.…”
Section: Pharmacological Therapymentioning
confidence: 77%
“…In fact, phytochemical screening of this extract revealed the presence of tannin, saponin, flavonoids, phenols, and coumarins [ 43 , 44 ]. Most of these biometabolites, such as flavonoid [ 45 , 46 ] and saponins [ 47 ], promote bone regeneration, while coumarins increase bone morphogenic protein-2 expression and thus enhance bone formation [ 48 ]. Moreover, these secondary metabolites particularly flavonoids, and phenols [ 49 , 50 ] are classes of compounds recognized for their ability to trap ROSs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, phytochemical screening of this extract revealed the presence of tannin, saponin, favonoids, phenols, and coumarins [43,44]. Most of these biometabolites, such as favonoid [45,46] and saponins [47], promote bone regeneration, while coumarins increase bone morphogenic protein-2 expression and thus enhance bone formation [48]. Moreover, these secondary metabolites particularly * p < 0.05, * * p < 0.01, and * * * p < 0.001: signifcantly diferent compared to the normal control group; a p < 0.05, c p < 0.001: signifcantly diferent compared to the alcohol control (1 or 2) group.…”
Section: Discussionmentioning
confidence: 99%